THE ROLE AND ROLE OF WATER NETWORKS IN THE IMPLEMENTATION OF IRRIGATION AND MELIORATION WORKS IN SURKHANDARYA - Soatmumin BURIEV (Scholar Express Journal, 2023)
This article talks about irrigation and reclamation works in Surkhandarya region. Extensive scientific research conducted in the oasis, as well as material sources found in the course of archaeological excavations, provide sufficient information about this. Today, the role of water networks in the flourishing of the SurkhanSherabad oasis, as well as the functioning of existing reservoirs in the oasis, has been sufficiently discussed
Keywords: Southern Surkhan Reservoir; Sherabad Joint Stock Company; agro-industrial complex